Beyond empire and nation : the decolonization of African and Asian societies, 1930s-1960s - Bogaerts, Els; Raben, Remco (Leiden : KITLV Press, 2012)
This monograph is a publication of the research programme'Indonesia across Orders. The reorganization of Indonesian society.'
Includes bibliographical references and index.
Keywords: Decolonization -- Africa; Decolonization -- Asia